Physician challenges and supports during the first wave of the COVID-19 pandemic: A mixed methods study - Williams, Myia S.; Ryniker, Laura; Schwartz, Rebecca M.; Shaam, Pooja; Finuf, Kayla D.; Corley, Samantha S.; Parashar, Nidhi; Young, John Q.; Bellehsen, Mayer H.; Jan, Sophia (Frontiers in Psychiatry, 2022)
During the COVID-19 pandemic, physicians encountered significant COVID-19-related negative experiences and psychological distress in both their personal and professional lives. To understand the factors that negatively impact physician well-being, a number of studies have pointed to multiple work system factors such as excessive workload and workflow interruptions. In addition, studies have shown that positive interpersonal relationships that provide social support may also serve as a buffering role against psychological distress. Using both qualitative and quantitative data collected immediately following the first wave of COVID-19, our study explores the challenges and sources of support for physicians relative to mental health symptoms. Of the 457 physicians in the study, the most frequently potential negative occupational experiences were, “Being at risk of contracting COVID-19 from patients/co-workers” (90.5%) and “Contact with distressed family members who cannot be with a loved one” (69.5%). We identified five common themes for main sources of social support (e.g. emotional support from family/friends) and six themes for challenges (e.g., work-related demands exacerbated by the pandemic).